Co-Ordination of Parallel GRID Applications using Synchronizers - Kopanski, D.; Borkowski, J.; Tudruj, M. (International Conference on Parallel Computing in Electrical Engineering (Parelec 2004, 2004)
Recently, the graphical parallel programming environment P-GRADE based on message passing has been extended by advanced synchronization and control mechanisms (synchronizers) based on predicates computed on consistent application global states (PS-GRADE). In the new P-GRADE Workflow system, the application workflow has been introduced to enable designing control flow between otherwise independent applications. In this paper, we propose that program execution control by synchronizers can be extended and used to coordinate parallel applications executed on GRID in the frame of a PS-GRADE tool. We introduce explicit inter-application, or GRID-level, synchronizers. They are connected to application level synchronizers, which are able to send state reports and receive control signals over GRID communication network. Open Grid Services Infrastructure, implemented using Globus toolkit, is proposed to be used for these purposes.